Use of miRNA Sequencing to Reveal Hub miRNAs and the Effect of miR-582-3p/SMAD2 in the Progression of Hepatocellular Carcinoma - Zhao, Yi; Li, Meizhang; Miao, Nana; Wei, Wei; Dong, Yulong; Tao, Chenjie; Chen, Jinzhong; Pei, Yongyan; Guo, Lieping (Frontiers in Genetics, 2022)
Hepatocellular carcinoma is a common tumor with a high fatality rate in the world, and exploring its pathogenesis and deterioration mechanism is the focus of many researchers. More and more evidences show that miRNA is involved in the occurrence and progression of a variety of cancers, including hepatocellular carcinoma. Therefore, this project is mainly to identify key miRNAs related to hepatocellular carcinoma and explore its potential functions and clinical significance. In this study, we performed miRNA sequencing on 3 pairs of hepatocellular carcinoma tissue samples and screened 26 differentially expressed miRNAs. Then 2 key miRNAs (miR-139-5p and miR-582-3p) were screened by Kaplan-Meier curve analysis, Cox multivariate analysis and qPCR methods. And the expression of miR-582-3p is positively correlated with clinicopathological parameters in patients with hepatocellular carcinoma. Subsequently, miRwalk and Starbase were used to predict the target genes of key miRNAs, then the key pairs miR-582-3p/SMAD2 was obtained by WGCNA, PPI, qPCR and Pearson correlation analysis. Finally, the dual luciferase experiment, the rescue-of-function experiment and qPCR confirmed that miR-582-3p directly targets SMAD2 and regulates the proliferation, migration and invasion of Sk-Hep-1 cells by targeting SMAD2. At the same time, interference with SMAD2 can affect the effect of miR-582-3p on Sk-Hep-1 cells. In conclusion, our findings confirm that miR-582-3p is an independent factor for the prognosis of hepatocellular carcinoma patients, and can regulate the progression of hepatocellular carcinoma cells by targeting SMAD2.